Co-application of ACC-deaminase producing PGPR and timber-waste biochar improves pigments formation, growth and yield of wheat under drought stress - Danish, Subhan (Sci Rep, 2019)
Besides other deleterious effects, drought elevates ethylene level too in plants. Increased ethylene concentration reduces root elongation and development that consequently retard plant growth and yield. There are certain PGPR which produce ACC-deaminase. The ACC-deaminase converts ACC (an immediate precursor of ethylene biosynthesis in methionine pathway in higher plants) into ammonia and α-ketobutyrate instead of ethylene. Regularization of ethylene level in plants mitigate the effects of drought. On the other hand, biochar has been reported to be rich in nutrients and exhibiting higher water holding capacity. So, a pot study was conducted with the hypothesis that the combined application of ACC-deaminase producing PGPR and biochar would minimize the drought effects on wheat growth. The ACC-deaminase producing PGPR were applied on wheat seeds in combination with two biochar doses. Three moisture levels were maintained throughout the trial. The data obtained revealed that B. amyloliquefaciens + 2BC improved the chlorophyll a, chlorophyll b, photosynthetic rate, transpiration rate, 100-grain weight, and grain N, P and K up to 114%, 123%, 118%, 73%, 59%, 58%, 18% and 23%, respectively, under drought conditions. It is concluded that co-application of PGPR and biochar is an effective technique to mitigate the drought effects.